2017
DOI: 10.1021/acsomega.7b01420
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature and Solution-Processable Zinc Oxide Transistors for Transparent Electronics

Abstract: Zinc oxide (ZnO) thin-film transistors (TFTs) have many promising applications in the areas of logic circuits, displays, ultraviolet detectors, and biosensors due to their high performances, facile fabrication processing, and low cost. The solution method is an important technique for low-cost and large fabrication of oxide semiconductor TFTs. However, a key challenge of solution-processable ZnO TFTs is the relatively high processing temperature (≥500 °C) for achieving high carrier mobility. Here, facile, low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 32 publications
1
30
1
Order By: Relevance
“…The excess oxygen generally decreases when a higher temperature was used, such as from 40.1 % to 28.8 % at 350 °C, except at 300 °C where the percentage of excess oxygen is 50.3 %. This result is complied with previous study [227]. It is suggested that the excess oxygen mainly converts to oxygen vacancies at a temperature lower than 300 °C.…”
Section: Surface Defect Studysupporting
confidence: 93%
See 2 more Smart Citations
“…The excess oxygen generally decreases when a higher temperature was used, such as from 40.1 % to 28.8 % at 350 °C, except at 300 °C where the percentage of excess oxygen is 50.3 %. This result is complied with previous study [227]. It is suggested that the excess oxygen mainly converts to oxygen vacancies at a temperature lower than 300 °C.…”
Section: Surface Defect Studysupporting
confidence: 93%
“…The sub-peak at 531.0 eV is associated with oxygen vacancies and is denoted as O2. The sub-peak located at the highest binding energy is associated with surface-adsorbed oxygen-containing species and is denoted as O3 [111,227].…”
Section: Time-resolved Photocurrentmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium binding energy component O V , centered at 531.2 eV, is associated with O 2− ions in the oxygen‐deficient regions within the Mg x Zn 1 − x O matrix. [ 34,35 ] Therefore, variation in intensity/area of the O V component indicates the change in concentration of oxygen vacancy in the film matrix. It can be clearly seen from Figure 6a,b that the relative intensity/area of the O V peak decreases as the oxygen ambient pressure increases from 1.0 × 10 −2 to 1.0 × 10 −1 mbar, indicating a decrease in the concentration of oxygen vacancies at higher oxygen growth pressures leading to low free carrier concentration.…”
Section: Resultsmentioning
confidence: 99%
“…These advantages of inkjet printing have been widely employed for the fabrication of semiconductor devices [3,4]. Thanks to its outstanding features and abundance, zinc oxide (ZnO) has attracted considerable attention and effort in the additive fabrication of electronics devices such as solar cells [5,6], photodetectors [3,7], and transistors [8,9]. Additive manufacturing of inorganic material from a precursor compound usually requires a heat treatment step in order to convert precursors to the required material [10,11].…”
Section: Introductionmentioning
confidence: 99%